Thermally driven cross-shore flows in stratified basins: a review on the thermal siphon dynamics - Damien Bouffard; Tomy Doda; Cintia L. Ramón; Hugo N. Ulloa (Flow, 2025)
The sloping boundaries of stratified aquatic systems, such as lakes, are crucial environmental dynamic zones. While the role of sloping boundaries as energy dissipation hotspots is well established, their contribution to triggering large-scale motions has received less attention. This review delves into the development of thermally driven cross-shore flows on sloping boundaries under weak wind conditions. We specifically examine ‘thermal siphons’ (TS), a dynamical process that occurs when local free convection transforms into a horizontal circulation over sloping boundaries. Thermal siphons result from bathymetrically induced temperature (i.e. density) gradients when a lake experiences a uniform surface buoyancy flux, also known as differential cooling or heating. In the most common case of differential cooling of waters above the temperature of maximum density, TS lead to an overturning circulation characterised by a downslope density current and a surface return flow within a convective environment. Field observations, laboratory experiments and high-fidelity simulations of TS provide insights into their temporal occurrence, formation mechanisms, water transport dynamics and cross-shore pathways, addressing pivotal questions from an aquatic system perspective. Fluid mechanics is a fundamental tool in addressing such environmental questions and thereby serves as the central theme in this review.